2020
DOI: 10.3390/ijms21176094
|View full text |Cite
|
Sign up to set email alerts
|

UDP-GLYCOSYLTRANSFERASE 72E3 Plays a Role in Lignification of Secondary Cell Walls in Arabidopsis

Abstract: Lignin is present in plant secondary cell walls and is among the most abundant biological polymers on Earth. In this work we investigated the potential role of the UGT72E gene family in regulating lignification in Arabidopsis. Chemical determination of floral stem lignin contents in ugt72e1, ugt72e2, and ugt72e3 mutants revealed no significant differences compared to WT plants. In contrast, the use of a novel safranin O ratiometric imaging technique indicated a significant increase in the cell wall lignin cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 61 publications
0
17
1
Order By: Relevance
“…Functional characterization of mutants has evidenced phenotypes to clarify this question. Although single ugt72e1, ugt72e2 or ugt72e3 Arabidopsis mutants do not show any difference in lignin quantity in the floral stem when using the acetyl bromide method, a higher proportion of lignin in the xylem and interfascicular fiber cell walls of the ugt72e3 mutant was evidenced by Raman microspectroscopy and safranin O ratiometric imaging technique, as compared to the wild type [40]. This difference was only observed in the young part and not in the old part of the floral stem and indicates a role of UGT72E3 in cell wall lignification during vascular cells development.…”
Section: Regulation Of Lignificationmentioning
confidence: 85%
See 3 more Smart Citations
“…Functional characterization of mutants has evidenced phenotypes to clarify this question. Although single ugt72e1, ugt72e2 or ugt72e3 Arabidopsis mutants do not show any difference in lignin quantity in the floral stem when using the acetyl bromide method, a higher proportion of lignin in the xylem and interfascicular fiber cell walls of the ugt72e3 mutant was evidenced by Raman microspectroscopy and safranin O ratiometric imaging technique, as compared to the wild type [40]. This difference was only observed in the young part and not in the old part of the floral stem and indicates a role of UGT72E3 in cell wall lignification during vascular cells development.…”
Section: Regulation Of Lignificationmentioning
confidence: 85%
“…Moreover, a higher capacity of incorporation of the three fluorescently labeled monolignols into lignin was found in the ugt72e3 young stem as compared to the wild type. This phenotype was related to an increased expression of lignin-specific PRX71 and LAC17 [40]. The ugt72b1 mutant exhibits a higher lignin content in the whole floral stem, as well as an ectopic lignification in the interfascicular fibers and the pith as compared to the wild type and the rescued line (insertion of the UGT72B1 cDNA under the control of the native gene promoter) [39].…”
Section: Regulation Of Lignificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Histochemical assays and thioacidolysis analysis confirmed the enhanced lignification and increased lignin biosynthesis in the ugt72b1 mutant [ 33 ]. Recent research has found that the use of a novel safranin O ratiometric imaging technique indicated a significant increase in the cell wall lignin content of both interfascicular fibres and xylem from young regions of ugt72e3 mutant floral stems [ 34 ].…”
Section: Introductionmentioning
confidence: 99%